Effect of Axial Length on Macular Ganglion Cell Complex Thickness and on Early Glaucoma Diagnosis by Spectral-Domain Optical Coherence Tomography. Issue 5 (May 2016) - Nakanishi, Hideo; Akagi, Tadamichi; Hangai, Masanori; Kimura, Yugo; Suda, Kenji; Hasegawa, Tomoko; Yamada, Hiroshi; Yoshikawa, Munemitsu; Morooka, Satoshi; Ikeda, Hanako Ohashi; Yoshimura, Nagahisa
Abstract : Purpose: To investigate the effects of the axial length (AL)-related ocular magnification on the thickness of the macular ganglion cell complex (mGCC), and the diagnostic accuracy of the built-in normative database of the spectral-domain optical coherence tomographic (SD-OCT) instrument for early glaucoma detection. Methods: This retrospective study included 41 eyes with early primary open-angle glaucoma and 36 normal eyes. The mGCC thickness within a 20-degree circle, equivalent to a 6 mm diameter in the Gullstrand model eye, was measured in the SD-OCT images. The magnification effect was corrected using Bennett formula, and the mGCC thickness within the actual 6 mm diameter circle was determined. Results: In normal eyes, the inferior corrected mGCC was significantly correlated with the AL (β=−0.40, P =0.028), but correction for the magnification reduced the correlation. In 38 nonhighly myopic eyes, the sensitivity and specificity of the SD-OCT's significance maps for distinguishing early glaucoma were 95.0% and 94.4% when using either the uncorrected or the corrected mGCC. In 39 highly myopic eyes, the diagnostic accuracy was lower when using the uncorrected mGCC thickness (sensitivity was 95.2% and specificity was 44.4%), and was not improved when using the corrected mGCC (81.0% and 61.1%, respectively). Conclusions: The inferior mGCC was thinner in eyes with longer AL. The accuracy of the diagnosis with the SD-OCT built-in normative database for early glaucoma was not improved significantly by the correction of the AL-associated magnification in highly myopic eyes. Evaluation of highly myopic eyes with the nonhighly myopic normative database can lead to misdiagnosis. Abstract : Supplemental Digital Content is available in the text.